Combination of standardised methods to create a detailed source-based reconstruction of the Tepidarium at L’Alcudia de Elche, Alicante, Spain - Cristina Gonzalez-Esteban (Groma)
This study proposes a combined method for Virtual Archaeological Reconstructions (Extended Matrix, Reconstructive Units and Evidence Graphic Scale) to ease understanding, recording and display of archaeology. It aims to create new questions and challenges to increase knowledge. The Tepidarium project at L’Alcudia de Elche, Spain, showed the need to reduce duplicity and quicken the workflow; however, it increases the possibility of comparative studies due to similar results in other projects.